THE “RETURN” OF E.E. LANSERE FROM THE CAUCASUS: the review of P. Pavlinov’s study on the Caucasian period in the life of the artist (1912-1934) - Tahnaeva, Patimat Ibragimovna (History, Archeology and Ethnography of the Caucasus, 2020)
The review is devoted to a monograph about the stay of one of the most significant masters of the St. Petersburg Association "World of art" E. E. Lancer on the territory of the North Caucasus and Transcaucasia during a difficult time of transformation and change of power, numerous projects and trips of the artist both in the Caucasus region and abroad (in Anatolia, France, Moscow, Leningrad, Kharkiv, Rostov-on-don), the emergence of his interest in traveling and preserving his love for Georgia, Armenia, Dagestan and other republics from the 1910s until his death in 1946.